2019
DOI: 10.4103/tjo.tjo_108_18
|View full text |Cite
|
Sign up to set email alerts
|

Step-by-step Descemet's membrane endothelial keratoplasty surgery

Abstract: With the success of Descemet's stripping automated endothelial keratoplasty (DSAEK) technique providing better outcomes in visual prognosis and theoretically lower rejection rate than penetrating keratoplasty, DSAEK dominated the realm of endothelial keratoplasty for the past decade. However, Descemet's membrane endothelial keratoplasty (DMEK) has become more and more popular worldwide due to its even lower rejection rate, faster visual recovery, better visual outcome, and lower long-term endothelial loss. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…The DM roll was manipulated meticulously and gently using no-touch tapping and fluid wave techniques until it was opened in the correct orientation. 31 , 32 A handheld slit beam and endoilluminator were used intraoperatively to determine the graft orientation. 33 The DM graft was then centered and fully unscrolled.…”
Section: Methodsmentioning
confidence: 99%
“…The DM roll was manipulated meticulously and gently using no-touch tapping and fluid wave techniques until it was opened in the correct orientation. 31 , 32 A handheld slit beam and endoilluminator were used intraoperatively to determine the graft orientation. 33 The DM graft was then centered and fully unscrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the endothelial cells are damaged whenever the donor lenticule touches the IOL surface or during any manipulation performed with a surgical instrument. 1,7 The suture knots and tails have a similar potential to destroy or damage the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bei der erst 2006 beschriebenen DMEK wird nur die Descemet-Lamelle mit der Endothelzellschicht transplantiert. Bereits durchgeführte Studien zeigten, dass die DMEK in Bezug auf die Indikation Fuchs-Endotheldystrophie (FED) gegenüber der PKP gravierende Vorteile bietet [2,5].…”
Section: Ergebnisse Insgesamt Traten Im Beobachteten Zeitraum 54unclassified
“…In DMEK, which was only described in 2006, only the Desce-metʼs lamella with the endothelial cell layer is transplanted. Previous studies have shown that DMEK offers serious advantages over PKP for the indication Fuchs endothelial dystrophy (FED) [2,5]. Acute endothelial cell loss after keratoplasty is caused by the trauma of the operation (surgery) and endothelial immune reactions.…”
Section: Introductionmentioning
confidence: 99%